SV-wave with external force in saturated medium - Siang, T.L. (Penerbit UTM Press, 2016)
There are past researches done for SV-wave with the absence of external force. This work aims to investigate the influence of external force in the propagation of SV-wave in the soluble and insoluble mediums. Isotropic wave model is derived for SV-wave with various forces in accordance to Duhamel Principle and their analytical solutions are used to compare with each otherâsâ amplitudes. With the existence of high density fluid, diffusive waves with larger external force will induce higher amplitude. However, SV-waves are non-diffusive in low density medium and hence, this work concludes that wave diffusion by external force is subjected to the properties of the targeted medium. Â© 2016 Penerbit UTM Press. All rights reserved.